Surgical Strategy for Sternal Closure in Patients with Surgical Myocardial Revascularization Using Mammary Arteries - Mircea Robu; Bogdan Rădulescu; Irina Margarint; Ovidiu Știru; Iulian Antoniac; Daniela Gheorghiță; Cristian Voica; Claudia Nica; Mihai Cacoveanu; Luminița Iliuță; Vlad Anton Iliescu; Horațiu Moldovan (Journal of Cardiovascular Development and Disease, 2023)
Background: Coronary artery bypass grafting has evolved from all venous grafts to bilateral mammary artery (BIMA) grafting. This was possible due to the long-term patency of the left and right internal mammary demonstrated in angiography studies compared to venous grafts. However, despite higher survival rates when using bilateral mammary arteries, multiple studies report a higher rate of surgical site infections, most notably deep sternal wound infections, a so-called “never event”. Methods: We designed a prospective study between 1 January 2022 and 31 December 2022 and included all patients proposed for total arterial myocardial revascularization in order to investigate the rate of surgical site infections (SSI). Chest closure in all patients was performed using a three-step protocol. The first step refers to sternal closure. If the patient’s BMI is below 35 kg/m2, sternal closure is achieved using the “butterfly” technique with standard steel wires. If the patient’s BMI exceeds 35 kg/m2, we use nitinol clips or hybrid wire cable ties according to the surgeon’s preference for sternal closure. The main advantages of these systems are a larger implant-to-bone contact with a reduced risk of bone fracture. The second step refers to presternal fat closure with two resorbable monofilament sutures in a way that the edges of the skin perfectly align at the end. The third step is skin closure combined with negative pressure wound therapy. Results: This system was applied to 217 patients. A total of 197 patients had bilateral mammary artery grafts. We report only 13 (5.9%) superficial SSI and only one (0.46%) deep SSI. The preoperative risk of major wound infection was 3.9 +/− 2.7. Bilateral mammary artery grafting was not associated with surgical site infection in a univariate analysis. Conclusions: We believe this strategy of sternal wound closure can reduce the incidence of deep surgical site infection when two mammary arteries are used in coronary artery bypass surgery.